Softball pitchers` body segment girths are associated with varied biomechanics at ball release of the pitch - Friesen, K. B.; Oliver, G. D. (Medicine & Science in Sports & Exercise, 2023)
Purpose The purpose of this study was to examine the relationships between pitcher trunk and throwing arm girth with kinematics at ball release of the softball pitch. Softball pitchers can be of various shapes and sizes; however, it is unknown if segment girth might influence pitch biomechanics. Because of the importance of body positioning at ball release of the windmill pitch, this study examined the relationship between segment girth and pitch biomechanics at ball release.